Caracterização dos Genótipos do HIV em doadores de sangue soropositivos da Fundação de Hematologia e Hemoterapia do Amazonas. - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
The Human Immunodeficiency Virus (HIV) is characterized by a wide genetic diversity. Two types of HIV are recognized at present: HIV-1 and HIV-2. The HIV-1, responsible for most of the cases of AIDS in the world, is divided in three groups denominated M (Major), O (Outlier) and N (Non-M/Non-O), and until this moment nine subtypes of the group M (A-D, F-H, J-K) were already identified. Beyond of those subtypes, the HIV-1 also have been classified in circulating recombinant forms (CRFs) and unique recombinant forms (URFs). In Brazil, a pattern complex of distribution of those subtypes has been described in their different geographical areas. In search of elucidating the predominant subtypes of HIV-1 in the city of Manaus, this study had as objective to analyze blood samples of subjects that presented results positive or indeterminate for HIV, in the systematic selection of blood donors of the Fundação de Hematologia e Hemoterapia do Amazonas (HEMOAM). In the moment of the collect, the donors registered their authorization by the signature of the free consent and knowledge term and they answered a questionnaire used for epidemic data investigation. DNA proviral extracted of the samples with indeterminate/positive resulted in Western Blot was submitted a Polimerase Chain Reaction in two stages (Nested PCR) for the confirmation of the HIV-I infection. The amplified products (regions gag, pol and env) of the 31 samples reactivate for PCR were automatically sequencing and analyzed phylogenetically by the Phylip program. All of the indeterminate samples for the confirmatory test presented negative amplification pattern. Of the reactivates samples for HIV in the confirmatory test and PCR, it was observed male predominance (77,4%) and in the donors of first time (67,7%). Among the repetition donors, 60% presented seroconvertion in up to 20 months. Of the total of samples, was identified the predominance of the subtype B (87,1%), following by the subtype C (6,5%), F (3,2%) and recombinant BF (3,2%). The amino acids sequences of 19 isolated were analyzed for the genetic variability characterization of the region of the loop V3. Among the isolated of the subtype B, the tetrapeptide more prevalente was GPGR (68,4%), following by the Brazilian variant B" GWGR (15,8%). The Subtype C occurrence in the North Region still was not reported in the literature. The analyses of similarity of the isolated of the subtype C in this study demonstrated larger similarity of these with other isolated ones brazilian, in relation to isolated in other parts of the world. Our results can contribute to a better understanding of the characteristics of the lineages of the HIV-1 circulating in Brazil, information that can be used in benefit of the diagnosis, treatment, control of the disease and preparation of vaccines.
Keywords: HIV-1; Subtipos; PCR; Genotipagem; HIV-1; Subtypes; PCR; Genotyping; CIÊNCIAS BIOLÓGICAS